Effects of VR Presence on Health Risk Perceptions - Choe, Min-Ji; Noh, Ghee-Young (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study aimed to examine the effects of presence in VR video on changes in health risk perceptions – health self-efficacy, perceived susceptibility, and perceived severity – about infectious disease prevention behavior.Methods/Statistical analysis: The experiment was conducted to observe whether participants perceived health behavior differently after watching VR video about washing hands. Participants were consisted of 75 males and 75 females and they were asked to fill out the pre-questionnaire about health perceptions before watching VR video and post-questionnaire after watching the video. The collected data were analyzed by R-MONOVA to examine the interaction effect of gender and the VR video presence.Findings: The results showed that the VR video presence had significant impacts on changes in health risk perceptions not only at multivariate level but also at univariate level. The results of this study imply that the effect of presence in VR video can influence the changes of health perceptions and eventually it can make individuals behave in healthy way. In addition, gender influenced the changes of health risk perceptions only at multivariate level but it did not cause any change at univariate level. Most of all, the interaction effect of gender and the presence of VR video only appeared at univariate level. Especially, perceived severity was affected by the interaction effect. Since perceived severity was changed depending on not gender but the effect of presence when analyzing separately, it implies that experience in VR can be different according to gender group. This study proved that the vividness effect of VR video was persuasive in changing health risk perceptions and it can be used in health industry to promote healthy behavior.Improvements/Applications: This study was improved in suggesting the effect of presence on changes of health perceptions according to gender. Thus, differences in presence depending on gender should be taken into consideration.